IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN KARAKTER RELIGIUS PESERTA DIDIK DI SEKOLAH MENENGAH PERTAMA - Diana; Dina Rahma Dayanti; Muhammad Fiqri; Sarinah; Mukhtar Latif (STKIP Subang, 2026)
The implementation of the Merdeka Curriculum at the junior high school level opens opportunities for Islamic Religious Education teachers to design lessons that are more contextual and focused on character building. This study aims to describe the implementation of the Merdeka Curriculum in Islamic Religious Education and to analyze its contribution to strengthening students’ religious character, particularly through the Pancasila Student Profile Strengthening Project (P5) and differentiated instruction. The study employed a qualitative case study approach, using data collection techniques such as classroom observations, in-depth interviews with teachers and students, and document analysis at a junior high school. The results of the study indicate that the Merdeka Curriculum encourages teachers to shift from a lecture-based approach toward learning that is experiential, reflective, and project-based, such as Quran recitation (tadarus), religious mentoring, and social service activities directly linked to daily worship practices. Students demonstrated improvement in indicators of religious character, including discipline in worship, honesty, tolerance, and social concern, although challenges were still identified regarding teacher readiness, the assessment of affective aspects, and limitations in the allocation of instructional time. This study concludes that the Merdeka Curriculum provides a flexible framework and, when supported by adequate teacher competencies and a conducive school culture, is capable of meaningfully strengthening students’ religious character